Factors Influencing Philanthropic Behavior among Youths in Malaysia - Sukri, Norellani Binti; Mohamad Arshad, Afiza Azura; Cheng, Chuah Soo; Mohd Aminuddin, Zaidi; Arshad, Azlin Shafinaz (Information Management and Business Review, 2023)
Philanthropy is the desire to promote the well-being of others. It is about looking for and helping the welfare of others, particularly by giving them money for good reasons. Philanthropy is not only confined to the contribution of money, but it involves making efforts for religious purposes and self-satisfaction towards others. The level of charity among Malaysian citizens is alarming in 2015, Malaysia ranked 10th in the World Giving Index but in 2021 the ranking has dropped tremendously to 29th place. This has shown that Malaysians are getting less interested in participating in charitable activities and doing general good deeds. Therefore, there is an urgent need to look broadly at the philanthropic behavior of Malaysians. This research aims to determine the factors influencing philanthropic behavior among youth in Malaysia. For this study, a survey was conducted to the target population which is youth. Data was collected by distributing questionnaires via emails and WhatsApp groups and data was analyzed using SPSS and PLS-SEM. Findings show that religion and altruism are significant to the philanthropic behavior of Malaysian youth. This study has provided valuable insights into youth philanthropy by identifying solutions to further create awareness of philanthropy.